A Study of Closed-House Systems in Broiler Production - Handayani Indah Susanti (Department of Agribusiness, Halu Oleo University Jointly with Perhimpunan Ekonomi Pertanian Indonesia - Indonesian Society of Agricultural Economics (PERHEPI/ISAE), 2023)
This study aims to determine broiler chickens' production performance in a closed-house system. The research was conducted in a closed-house system with a capacity of 22,000 CP 707 strains at plasma breeders of PT. Prosperous Star Together. The variables used in this study include harvested body weight, body weight gain, Feed Conversion Ratio (FCR), Performance Index (IP) and percentage of depletion. The research technique used is direct observation in the field. Sampling uses simple random sampling, where the sample is randomly selected from a specified number. Analysis tools used descriptive method. The measurement data will be compared with the performance standards of broiler chickens according to PT. Charoen Pokphand. The results showed that the average body weight at 25 days was 1.614 kg/head, increased body weight was 1.564 kg/head, FCR was 1.36, IP was 465.45 and depletion percentage was 1.95%. The conclusion that can be drawn from the results of this study is that the production performance of broiler chickens kept in a closed-house system reaches the standards of PT. Charoen Pokphand.